2009
DOI: 10.1111/j.1468-0084.2008.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Fertility Patterns*

Abstract: Recent studies by economists have focused on cultural transmission from the origin country rather than the origin family. Our paper extends this research by investigating how "family-specific"'cultural transmission' can affect fertility rates. Following Machado and Santos Silva ["Journal of the American Statistical Association" (2005) Vol. 100, p. 1226] and Miranda ["Journal of Population Economics" (2008) Vol. 21, p. 67], we estimate count data quantile regression models using the British Household Panel Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 48 publications
2
61
0
1
Order By: Relevance
“…The interdependence between fertility and spatial mobility is now also part of the research agenda (e.g., Kulu and Milewski 2007;Meil 2010a;Huinink and Feldhaus 2012). The connection between the past, present and future of the life course is recognized in analyses of the effects of individual life experiences (e.g., Booth and Kee 2009;Hakim 2000;Hayford 2009;Noordhuizen, de Graf and Sieben 2011;Schröder and Brüderl 2008;Thomson 2002) and of perceived future risks for the household's welfare situation (e.g., Bernardi et al 2008;Kreyenfeld 2010;Sobotka et al 2011) on childbearing behavior or intentions. The multi-level embeddedness of the life course in societal structures has been emphasized as well (Mayer and Huinink 1990).…”
Section: Empirical Researchmentioning
confidence: 99%
“…The interdependence between fertility and spatial mobility is now also part of the research agenda (e.g., Kulu and Milewski 2007;Meil 2010a;Huinink and Feldhaus 2012). The connection between the past, present and future of the life course is recognized in analyses of the effects of individual life experiences (e.g., Booth and Kee 2009;Hakim 2000;Hayford 2009;Noordhuizen, de Graf and Sieben 2011;Schröder and Brüderl 2008;Thomson 2002) and of perceived future risks for the household's welfare situation (e.g., Bernardi et al 2008;Kreyenfeld 2010;Sobotka et al 2011) on childbearing behavior or intentions. The multi-level embeddedness of the life course in societal structures has been emphasized as well (Mayer and Huinink 1990).…”
Section: Empirical Researchmentioning
confidence: 99%
“…Fertility transmission has been found to be strongest for higher-parity families, i.e. families with three or more children (Booth and Kee 2009;, which can be conceived as an nonstandard family structure in societies characterized by low fertility (Boehnke, Hadjar, and Baier 2007). Strong patterns of intergenerational family formation transmission are expected to be associated with higher-parity families of origin.…”
Section: If the Central Mode Of Family Formation Transmission Occurs mentioning
confidence: 99%
“…Research has demonstrated that mothers' age at first birth is significantly associated with their children's age of birth in the United States (Barber 2001). Similarly, intergenerational transmission of fertility patterns have been established in Britain (Booth and Kee 2009) and other European countries (Murphy and Wang 2001;Murphy 2013). Vast research has also shown the association between parental divorce and children's likelihood to marry and divorce in the United States (Amato 1996;Amato and DeBoer 2001;Wolfinger 2003) as well as in other countries, such as Finland (Erola, Härkönen, and Dronkers 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A quite high proportion of Italian women may therefore be culturally oriented to stop work after a child is born, or may prefer to ask grandparents to look after the newborn baby. A family-oriented approach is also often transmitted from one generation to the next (see, e.g., Anderton et al 1987;Booth and Kee 2009) and family-oriented parents may in turn be the children of parents more willing to make themselves available to look after their grandchildren.…”
Section: Opportunity Cost Family Preferences and Strong Family Tiesmentioning
confidence: 99%